Viviendas unifamiliares, utilización de la madera (A+U, 1998)
<Fink + Jocher>: House, Alemania, 1995-1996; <Huber-Huber>: House, Alemania, 1990; <Andresen-O'Gorman>: Rosemary House, Australia; <Stelzhammer, W.>: Turkish House, 1983-2000